Glycemic control and serum albumin in type 2 diabetes patients: What does observational study say? - Nelvia Okta Yosa (Majalah Kedokteran Andalas, 2024)
Glycemic control is important to prevent organ damage in Type 2 Diabetes Melitus (T2DM) Patients, especially liver and kidney. One of parameter used to see the decreasing function of both organs is serum albumin. Aim : The aim of this study was to identify the association between glycemic control and serum albumin level on T2DM patoents. Method :  This is an observational analytical study using cross sectional design. This study was conducted at RSUP Dr. M. Djamil Padang using T2DM patients medical records on 2019-2021. The level of HA1c <7% was cathegorised as good glycemic control and Hb1c >7% was cathegorised as poor glycemic control. Results : The results showed that there was an association between glycemic control and serum albumin level on T2DM patients at RSUP Dr. M. Djamil Padang. Conclusion : Glycemic control was inversely associated with serum albumin levels in patients with T2DM in RSUP Dr. M. Djamil Padang